Perancangan TCAD (Tap Card Access Door) Menggunakan NFC Dengan Monitoring Berbasis Web : (Studi Kasus: Ruang Dekanat Fakultas Teknik Universitas Negeri Padang) - Afif Fadhilah; Geovanne Farell; Ahmaddul Hadi; Khairi Budayawan (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
The usage of manual keys in door security has become obsolete due to the increasing risk of theft and loss of valuable items. Observations at the Dean’s Office of the Faculty of Engineering at Universitas Negeri Padang reveal the shortcomings of manual key systems, including the possibility of getting stuck, lost keys, and the inability to record access. TCAD (Tap Card Access Door) offers a solution by utilizing NFC and cameras to directly monitor door access. This research aims to develop TCAD that can real-time monitor door access and store usage data. The development method for TCAD follows the waterfall model, and the system is designed using PHP with the Laravel framework, JavaScript, MySQL as the DBMS, and Visual Studio Code as the editor. Test results demonstrate that TCAD with NFC and web-based monitoring simplifies access entry recording, facilitates data collection during user room access, and improves data search efficiency. With TCAD, it is expected that door security and access monitoring can be better controlled and more efficient in line with current technological advancements.